2013
DOI: 10.1101/gr.154922.113
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive prediction in 78 human cell lines reveals rigidity and compactness of transcription factor dimers

Abstract: The binding of transcription factors (TFs) to their specific motifs in genomic regulatory regions is commonly studied in isolation. However, in order to elucidate the mechanisms of transcriptional regulation, it is essential to determine which TFs bind DNA cooperatively as dimers and to infer the precise nature of these interactions. So far, only a small number of such dimeric complexes are known. Here, we present an algorithm for predicting cell-type-specific TF-TF dimerization on DNA on a large scale, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 51 publications
(60 reference statements)
3
59
0
Order By: Relevance
“…6D). This motif, which resembles a FOXA1 motif described in another study (Jankowski et al 2013), aligns with the FOXA1 motif in both forward and reverse orientation, and the footprint profile for this palindromic sequence can be explained by FOXA1 binding in two orientations (Fig. 6D).…”
Section: Exoprofiler Applied To Other Chip-exo Datasupporting
confidence: 67%
See 1 more Smart Citation
“…6D). This motif, which resembles a FOXA1 motif described in another study (Jankowski et al 2013), aligns with the FOXA1 motif in both forward and reverse orientation, and the footprint profile for this palindromic sequence can be explained by FOXA1 binding in two orientations (Fig. 6D).…”
Section: Exoprofiler Applied To Other Chip-exo Datasupporting
confidence: 67%
“…Structural alignment of the homologous FOXK1 protein indicated that this motif can be simultaneously bound by two FOX proteins ( Fig. 6D; Jankowski et al 2013). However, since the footprint is derived from many cells, it might also reflect FOXA1 binding in one orientation for some cells and in the opposite orientation for others.…”
Section: Exoprofiler Applied To Other Chip-exo Datamentioning
confidence: 99%
“…This is consistent with previous observations that retrotransposons may contain multiple ancestral TF binding sites [88][89][90][91][92] ( Figure S14A). Among all motif pairs, the top 1% most frequent distances mapped in 83% to ERVs and were often larger than 20 bp (Figure S14B,C), which exceeds the typical distance between motifs found in composite motifs that promote TF cooperativity 93,94 . This suggests that over-represented strict motif spacings alone are not a reliable indicator for functional motif syntax.…”
Section: Figure 3 Discovery Of Composite Motifs and Indirect Bindingmentioning
confidence: 90%
“…There are FFLs with two TFs found by experimental work 61 and theoretical analyses 34, 62 . In addition to TF-TF FFLs, two TF regulators may form regulatory TF dimers 63 or more complex regulatory units to affect the downstream gene expression 64 .…”
Section: Discussionmentioning
confidence: 99%